The effects of vivifrail-based multicomponent training on physical and cognitive function in frail older adults: a systematic review and meta-analysis - Chen, Jiping; Liu, Haojie; Zhao, Haojie; Yao, Jiawei; Lu, Yanyu (Frontiers in Physiology, 2025)
ObjectivesVivifrail is a personalized, multicomponent exercise program that has emerged in recent years. This systematic review and meta-analysis aimed to assess the effects of Vivifrail-based multicomponent training on physical and cognitive function in frail older adults.MethodsA systematic search was conducted following the PRISMA guidelines, using the following databases: PubMed, Web of Science, The Cochrane Library, EBSCOhost, and Embase, covering studies up to 26 May 2025. The included studies were assessed for quality using the Effective Public Health Practice Project quality assessment tool. Data were analyzed using random-effects meta-analysis.ResultsTwelve studies, including 1,026 participants, were included in the meta-analysis. Vivifrail-based multicomponent training showed significant beneficial effects on the Short Physical Performance Battery (SPPB) (SMD = 0.90; 95% CI: 0.50, 1.30; P < 0.001; I2 = 88.1%), grip strength (SMD = 0.62; 95% CI: 0.37, 0.87; P < 0.001; I2 = 68.9%), and cognitive function (SMD = 0.60; 95% CI: 0.34, 0.86; P < 0.001; I2 = 56.9%) compared to the usual care group. No significant effects were observed on the Barthel Index of activities of daily living (ADL) (SMD = 0.87; 95% CI: −0.12, 1.85; P = 0.083; I2 = 95.7%). Furthermore, no significant risk of publication bias was detected for any outcomes.ConclusionCurrent evidence suggests that Vivifrail-based multicomponent training significantly improves physical and cognitive function. However, the results should be interpreted with caution due to high heterogeneity in the meta-analysis.Systematic Review Registrationidentifier CRD420251071483.